(untitled) (Ágora Journal, 2021)
The article aims to present a comparative analysis of the institutional history of Sergipe del Rei captaincy major (1590-1820) and Santa Catarina Island government (1738-1821). Observing similarities and differences regarding the legal-political status, subordination ties to higher governments, of their military leaders remuneration, as well as the main civil and military bodies that set up in them, we seek to identify the fundamental characteristics and the hierarchical position of these two establishments in the Portuguese administration structure in America.